Representation of Women in the Film Kartini (2017): Mary Wollstonecraft’s Liberal Feminism on the Issues of Education and Women’s Autonomy - Enggar Adelya Sentya Utari; Syamsul Sodiq (Raja Zulkarnain Education Foundation, 2026)
This study analyses how Mary Wollstonecraft’s liberal feminism is represented in the film Kartini (2017). It specifically examines the portrayal of educational equality, women’s rationality, and women’s autonomy within Javanese feudal culture. Employing a qualitative descriptive method, the research draws on dialogues, scenes, character expressions, and visual elements from Kartini (2017). Data were gathered through observation, note-taking, and documentation, and analysed through identification, classification, interpretation, and description, all grounded in Wollstonecraft’s liberal feminist perspective. The findings show that Kartini (2017) portrays liberal feminism through three core elements. First, educational equality is highlighted by depicting women’s struggles to access education within a restrictive feudal culture. Visuals such as books, journals, letters, seclusion rooms, and relevant dialogues illustrate the clash between modern education and Javanese tradition. Second, women’s rationality emerges through Kartini and other women who critically challenge traditions such as seclusion, arranged marriage, and prescribed social roles. Third, women’s autonomy appears in their efforts to assert control over their life choices amid familial and societal expectations. The film presents liberal feminism as an ongoing negotiation with, rather than a full rejection of, Javanese feudal values. Thus, Kartini (2017) frames education, rationality, and autonomy as key tools in women’s fight against patriarchy and feudalism.